Feasibility study for biogas integration into waste treatment plants in Ghana - Mohammed, M.; Egyir, I.S.; Donkor, A.K.; Amoah, Philip; Nyarko, S.; Boateng, K.K.; Ziwu, C. (Elsevier, 2017)
Biogas (anaerobic digestion) technology is one of the most viable renewable energy technologies today. However, its economic efficiency depends on the investment costs, costs of operating the biogas plant and optimum methane production. Likewise the profit level also rests on its use directly for cooking or conversion into electricity. The present study assessed the economic potential for a 9000 m3 biogas plant, as an alternative to addressing energy and environmental challenges currently in Ghana. A cost-benefit analysis of the installation of biogas plant at University of Ghana (Legon Sewerage Treatment Plant) yielded positive net present values (NPV) at the prevailing discount rate of 23%. Further the results demonstrate that installation of the plant is capital intensive. Biogas used for cooking was by far the most viable option with a payback period (PBP) of 5 years. Sensitivity analysis also revealed cost of capital, plant and machinery as the most effective factors impacting on NPV and internal rate of return (IRR).